Aβ1-42 promotes microglial activation and apoptosis in the progression of AD by binding to TLR4 - Rui-xia Dou; Ya-min Zhang; Xiao-juan Hu; Fu-Lin Gao; Lu-Lu Zhang; Yun-hua Liang; Yin-ying Zhang; Yu-ping Yao; Li Yin; Yi Zhang; Cheng Gu (Redox Biology, 2024)
Alzheimer's disease (AD) is one of the most common age-related neurodegenerative diseases and the most devastating form of senile dementia. It has a complex mechanism and no effective treatment. Exploring the pathogenesis of AD and providing ideas for treatment can effectively improve the prognosis of AD. Microglia were incubated with β-amyloid protein 1-42 (Aβ1-42) to construct an AD cell model. After microglia were activated, cell morphology changed, the expression level of inflammatory factors increased, cell apoptosis was promoted, and the expression of microtubule-associated protein (Tau protein) and related proteins increased. By up-regulating and down-regulating Toll-like receptor 4 (TLR4), the cells were divided into TLR4 knockdown negative control group(Lv-NC group), TLR4 knockdown group(Lv-TLR4 group), TLR4 overexpression negative control group(Sh-NC group), and TLR4 overexpression group(Sh-TLR4 group). The expression of inflammatory factors was detected again. It was found that compared with the Lv-NC group, the expression of various inflammatory factors in the Lv-TLR4 group decreased, cell apoptosis was inhibited, and the expression of Tau protein and related proteins decreased. Compared with the Sh-NC group, the expression of inflammatory factors in the Sh-TLR4 group increased, cell apoptosis was promoted, and the expression of Tau protein and related proteins increased. These results indicate that Aβ1-42 may promote microglial activation and apoptosis by binding to TLR4. Reducing the expression of TLR4 can reduce the occurrence of inflammatory response in AD cells and slow down cell apoptosis. Therefore, TLR4 is expected to become a new target for the prevention and treatment of AD.